Breeding and Healthcare Management Practices of Dairy Animals Followed by Farmers in Varanasi District of Uttar Pradesh - Sharma, Shelly; Kadian, K. S.; Meena, H. R. (Indian Journal of Dairy Science, 2023)
A field study and survey was conducted in the Varanasi district to find out the status of existing breeding and healthcare management practices followed by dairy farmers. A total of 80 farmers were selected from the 4 randomly selected blocks of the district and survey was done with the help of prepared interview schedule. Majority of the farmers (73.75%) always practised Artificial Insemination (A.I.) as a method of breeding for their dairy animals while mucus discharge was mostly used for detecting heat. About 24.00 per cent of farmers always followed deworming and 26.25 per cent always vaccinated their dairy animals against FMD and HS. Repeat breeding was a major reproductive problem in dairy animals faced always by about 75.00 per cent of the farmers and pregnancy diagnosis of dairy animals was practised by only about 42.50 per cent of the farmers.